Analisis Perilaku Portal Baja Dengan Kekakuan Tingkat Lunak (Soft Story) - Putri, Ade Septiani; Suryanita, Reni; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Structure with soft story effect will enlarge the lateral deformation and shear forces in the column so that the destruction of the columns is particularly vulnerable when subjected to thelarge forces. This research aims to analyse the actual structural behaviour affected by the earthquake load. The steel structure was design according to Indonesian Steel Structure Building Code (SNI 1729-2015) and also Indonesian Load Earthquake Resistance Code (SNI 1726-2012). To assess the structural behaviour, the Non-linier Time History Analysis (NLTH) was conducted using finite element software. The earthquake load employed to the structurewas modified Elcentro adjusted to goeology of Pekanbaru. The result showed that in structure with soft story had the maximum displacement of 97,13 mm in Y direction. Moreover, maximumshear forces observed on the structure with soft story mechanism increased by 42.13% and 37.80% on X and Y direction respectively compared to the previous floor without soft storymechanism. The result also showed that soft story mechanism affected to the dynamic responses of the structure.Keywords: soft story, earthquake, structure behaviour, time history analysis